2019
DOI: 10.1021/acs.jpca.9b03592
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonic Rovibrational Partition Functions at High Temperatures: Tests of Reduced-Dimensional Models for Systems with up to Three Fluxional Modes

Abstract: Curvilinear coordinate Monte Carlo phase space integration and a series of full-dimensional fitted potential energy surfaces are used to study the effectiveness of reduced-dimensional models for predicting rovibrational anharmonicity at high temperatures. Fully coupled and fully anharmonic, but classical, rovibrational partition functions Q are computed for 14 species with two or three fluxional modes (inversions or torsions) and as many as 30 degrees of freedom. These results are converted to semiclassical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…In our own recent studies comparing fully coupled and fully anharmonic Monte Carlo phase space integral partition functions with RRHO, separable 1DHR, and multidimensional HR models, we found that the error in the partition function using a 1DHR model increased from just 20%, on average, for systems with one fluxional mode (such as a torsion) to factors of 2 and 7 for systems with two and three fluxional modes, respectively. , These errors are in fact comparable in magnitude to those quantified in the same study for a single conformer RRHO model. (Note that E1 and E2 improve on the single conformer RRHO model by including the effects of multiple conformers, but such a multiconformer RRHO method was not tested in ref .) It is unknown how well conclusions drawn for stable species can be applied to the description of transition states, but we can say that it is generally more difficult to define and separate torsions for transition states (which necessarily have a variety of low-frequency motions, many of which cannot be straightforwardly described as torsions) than for stable species.…”
Section: Theorysupporting
confidence: 75%
See 1 more Smart Citation
“…In our own recent studies comparing fully coupled and fully anharmonic Monte Carlo phase space integral partition functions with RRHO, separable 1DHR, and multidimensional HR models, we found that the error in the partition function using a 1DHR model increased from just 20%, on average, for systems with one fluxional mode (such as a torsion) to factors of 2 and 7 for systems with two and three fluxional modes, respectively. , These errors are in fact comparable in magnitude to those quantified in the same study for a single conformer RRHO model. (Note that E1 and E2 improve on the single conformer RRHO model by including the effects of multiple conformers, but such a multiconformer RRHO method was not tested in ref .) It is unknown how well conclusions drawn for stable species can be applied to the description of transition states, but we can say that it is generally more difficult to define and separate torsions for transition states (which necessarily have a variety of low-frequency motions, many of which cannot be straightforwardly described as torsions) than for stable species.…”
Section: Theorysupporting
confidence: 75%
“…1DHR results are generally assumed to be more accurate, but we caution against this assumption for large systems, where the scaling of the accuracy of 1DHR approaches is not well-understood. In our own recent studies comparing fully coupled and fully anharmonic Monte Carlo phase space integral partition functions with RRHO, separable 1DHR, and multidimensional HR models, we found that the error in the partition function using a 1DHR model increased from just 20%, on average, for systems with one fluxional mode (such as a torsion) to factors of 2 and 7 for systems with two and three fluxional modes, respectively. , These errors are in fact comparable in magnitude to those quantified in the same study for a single conformer RRHO model. (Note that E1 and E2 improve on the single conformer RRHO model by including the effects of multiple conformers, but such a multiconformer RRHO method was not tested in ref .)…”
Section: Theorysupporting
confidence: 73%
“…The small error for our best a priori semiclassical model is notable, as errors of this magnitude (<30%) are characteristic of the best a priori semiclassical methods for kinetics, such as those for tunneling, 110 high-temperature anharmonicity, 111 and nonadiabatic treatments of intersystem crossing. 107,112 Errors of this magnitude in kinetics are likewise comparable to those of many kinetics measurements, thus positioning a priori semiclassical theories as competitive with experiment as practical sources of quantitative chemical kinetics data.…”
Section: Discussionmentioning
confidence: 90%
“…In principle is seems theoretically to be the most effective model for thermal decomposition. Note also usefulness of reduced-dimensionality models in the research of larger molecules [27].…”
Section: Introductionmentioning
confidence: 99%